Acute Toxicity Test of Polysaccharides Krestin from Coriolus versicolor Extract with Parameters of Hepatocyte Damages, SGPT and SGOT Enzyme in Mice - Andita Ayu Mandasari; Sri Puji Astuti Wahyuningsih; Win Darmanto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2015)
Coriolus versicolor is a mushroom that has polysaccharopeptide krestin (PSK) and polysaccharopeptide (PSP). Many reports showed that polysaccharide krestin as a compound which could reduce mutagen induction, radiation, and development of cancer spontaneusly. However, all substances entering in body could change become toxic depending on dosage. Therefore, this research was aimed to know the effects of PSK on hepatocyte damages, SGPT and SGOT enzymes. Polysaccharide krestin was given by intraperitoneal injection once with treatment groups as follow: K0, was given only saline; P1, was given 80 mg/kg BB PSK dosage; P2, was given 120 mg/ kg BB PSK dosage; P3, was given 160 mg/ kg BB PSK dosage; P4, was given 200 mg/ kg BB PSK dosage; dan P5, was given 240 mg/ kg BB PSK dosage. The results showed that PSK caused hepatic lesions, such as parenchymatous (hydrophic) degeneration of hepatocytes in groups P2 and P3, mild to moderate necrosis in group P4, and moderate to severe necrosis in group P5. Level of SGPT enzyme was not increased, butlevel of SGOT enzyme was increased in mice given 160 mg/ kg BB dosage with value 151,62 ± 26,62 IU/ L.